Information technology: an erosion of cataloguing and Classification practices? (2000)
Information is recognised as an-important tool to societal growth and development. It has even perversed the different ways people choose use to govern themselves. Democracy being one and the most popular form of government accepted by many countries is not excluded from the use of this important tool. The tool has, however, not been adequately explored for the entrenchment and promotion'' Of democracy in Nigeria. To achieve sustainability in democracy in this country, this paper advocates that the National Assembly Library should be proactive in its drive to gather and disseminate information; a more assertive and outward looking information deliver)' system should be established; information workers should anticipate demand for information and there should be a purposeful drive to acquire the ...information required by political actors. Also, necessary infrastructures for the computerisation and networking of relevant libraries should be put in place, while a database for books, periodicals, parliamentary bills and other that papers that can serve the needs of the executive, legislators, judiciary and even the electorate should be created